User Experience and Usability of Neumorphism and Gamification User Interface Designs in an HIV Self-Test Referral Program for Men Who Have Sex With Men: Prospective Open-Label Parallel-Group Randomized Controlled Trial - Tsz Ho Kwan; Denise Pui Chung Chan; Shui Shan Lee (JMIR Publications, 2022)
BackgroundDigital interventions have been applied for promoting HIV prevention and care among men who have sex with men (MSM). As user interface (UI) design plays a role in determining usability and user experience (UX), the intervention outcome could be affected. ObjectiveIn this study, we hypothesized that 2 UI design styles, namely gamification and neumorphism, could impact usability and be differentially preferred by distinct groups of MSM. MethodsA prospective parallel-group open-label randomized controlled trial was conducted in Hong Kong. Eligible participants were adult MSM recruited by the research team or referred by enrolled participants, who followed instructions for performing an HIV self-test and promoted its use within their social network. Participants were randomized in a 1:1 ratio into either a gamification or neumorphism arm, with primarily visual differences in the UI only. The primary outcome was usability measured by the System Usability Scale (SUS) between the 2 arms. Distinct characteristics of promoters in the 2 arms who gave an SUS score of 80 or above were identified. ResultsOf 463 MSM registered in the study, 232 and 231 were randomized to the gamification and neumorphism arms, respectively. Excluding those who did not request a self-test kit, data from 218 and 216 participants in the gamification and neumorphism arms, respectively, were analyzed (totally 434 participants). With a median SUS score of 80 overall, participants in the neumorphism arm gave a higher score (P<.001), with a higher proportion giving a promoter-level SUS score (P=.002). Promoters used social media for sex networking (P=.02), used pre-exposure prophylaxis in the preceding year (P=.006), had higher satisfaction in UI design (P<.001), and had made a self-test referral (P=.04). In general, higher usability was recorded among participants who were confident in performing the HIV self-test (P<.001), and this was associated with a promoter-level SUS score in both arms. While no other personal characteristics were associated with promoters in the neumorphism arm, those in the gamification arm had higher HIV-related knowledge (P=.01), preferred a specific partner body image type (P=.03), and progressed toward peer referral by completing online training (P=.04). ConclusionsBoth gamified and neumorphic UI designs were well-accepted by MSM. UX and satisfaction of UI were both crucial in influencing the willingness of MSM to promote the application by referring their peers in the community to participate. The simplistic visual design of neumorphism conferred a more general acceptance in the community, whereas gamification was preferred in certain MSM subcommunities. Appropriate UI/UX design should be considered when developing digital interventions targeting the MSM community. Trial RegistrationClinicalTrials.gov NCT04379206; https://clinicaltrials.gov/ct2/show/NCT04379206